Maternity leave and mothers' long-term sickness absence: Evidence from Germany - Nicole Guertzgen; Karsten Hank (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Exploiting unique German administrative data, we estimate the association between an expansion in maternity leave duration from two to six months in 1979 and mothers' post-birth long-term sickness absence over a period of three decades after childbirth. Using a regression discontinuity design, we first show that the leave extension caused mothers to significantly delay their return to work within the first year after childbirth. We then compare the number and length of spells of long-term sickness absence of returned mothers who gave birth before and after the change in leave legislation. Our findings suggest that among those returned, mothers subject to the leave extension exhibit a higher incidence of long-term sickness absence as compared to control mothers. This also holds true after controlling for observable differences in pre-birth illness histories. At the same time, there are no pronounced effects on mothers' medium-run labor market attachment following the short-run delay in return to work, which might rationalize a negative causal health effect. Breaking down the results by mothers' pre-birth health status suggests that the higher incidence of long-term sickness absence among the treated may be explained by the fact that the reform has facilitated re-entry of a negative health selection into the labor market.
urn:nbn:de:bsz:180-madoc-374541
Keywords: J10; J16; J18; 330; maternity leave policies; health; administrative data; regression discontinuity design